2011
DOI: 10.1200/jco.2010.33.2247
|View full text |Cite
|
Sign up to set email alerts
|

Natural Course of Insomnia Comorbid With Cancer: An 18-Month Longitudinal Study

Abstract: Insomnia is a frequent and enduring problem in patients with cancer, particularly at the syndrome level. Early intervention strategies, such as cognitive-behavioral therapy, could prevent the problem from becoming more severe and chronic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
254
5
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 307 publications
(277 citation statements)
references
References 18 publications
11
254
5
2
Order By: Relevance
“…Though the prevalence ranges vary depending on the study characteristics, cancer survivors have consistently reported higher rates of sleep problems compared than the general population (Savard and Morin, 2001;Schultz et al, 2005;Bardwell et al, 2008;Mulrooney et al, 2008;Savard et al, 2011;Zhou and Recklitis, 2014), which parallel with our findings. Notwithstanding the limits of knowledge on the exact mechanism across the cancer trajectory, cancer-related sleep problems covering difficulties initiating or maintaining sleep, dissatisfaction with sleep quality, and/or short sleep duration appear to begin with cancer diagnosis, inducing emotional challenges (i.e., anxiety and distress), and are easily exacerbated during cancer treatments such as chemotherapy, which continue through cancer survivorship (Palesh et al, 2012;Garland et al, 2014).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Though the prevalence ranges vary depending on the study characteristics, cancer survivors have consistently reported higher rates of sleep problems compared than the general population (Savard and Morin, 2001;Schultz et al, 2005;Bardwell et al, 2008;Mulrooney et al, 2008;Savard et al, 2011;Zhou and Recklitis, 2014), which parallel with our findings. Notwithstanding the limits of knowledge on the exact mechanism across the cancer trajectory, cancer-related sleep problems covering difficulties initiating or maintaining sleep, dissatisfaction with sleep quality, and/or short sleep duration appear to begin with cancer diagnosis, inducing emotional challenges (i.e., anxiety and distress), and are easily exacerbated during cancer treatments such as chemotherapy, which continue through cancer survivorship (Palesh et al, 2012;Garland et al, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…Evidence has indicated that sleep complaints primarily characterized by sleep disturbance and insomnia frequently occur among cancer survivors (Savard et al, 2011;Irwin, 2013;Irwin et al, 2013;Garland et al, 2014); yet is these problems are often overlooked in posttreatment care for cancer survivors (Ancoli-Israel, 2009). Though the prevalence ranges vary depending on the study characteristics, cancer survivors have consistently reported higher rates of sleep problems compared than the general population (Savard and Morin, 2001;Schultz et al, 2005;Bardwell et al, 2008;Mulrooney et al, 2008;Savard et al, 2011;Zhou and Recklitis, 2014), which parallel with our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A search on PubMed was conducted using the terms ("sleep initiation and maintenance disorders" OR "sle- Findings from multi-cancer site studies, which included men with prostate cancer, were used if they presented prostate cancer-specific information [21,22,[24][25][26] . However, studies that gave only the overall findings were excluded [23,27,28] .…”
Section: Methodsmentioning
confidence: 99%
“…Insomnia or sleep disturbances among men with prostate cancer has been investigated in both cross-sectional and longitudinal studies (Table 1) [8,14,15,17,18,21,24,25,[42][43][44][45][46][47][48] . Within cross-sectional studies, between 8% and 53% of men with prostate cancer were reported to experience insomnia [15,17,18,21,[42][43][44] .…”
Section: Prevalence Of Insomnia Among Men With Prostate Cancermentioning
confidence: 99%